Autologous stem cell transplantation in the treatment of Hodgkin's disease - Tarabar Olivera; Tukić Ljiljana; Stamatović Dragana; Balint Bela; Elez Marija; Ostojić Gordana; Tatomirović Željka; Marjanović Slobodan (Vojnosanitetski Pregled)
Background/Aim. High-dose chemotherapy with autologous stem cell transplantacion (ASCT) has shown to produce long-term disease-free survival in patients with chemotherapysensitive Hodgkin disease. The aim of the study was to evaluate efficacy of ASCT in the treatment of Hodgkin's disease. Methods. Between May 1997 and September 2008, 34 patients with Hodgkin's disease in median age of 25 (range 16-60) years, underwent ASCT. Autologous SCT were performed as consolidation therapy in one poor-risk patients with complete response (CR) and in 10 patients in partial remission (PR) after induction chemotherapy (32.5%), for chemosensitive relapse (CSR 1 and CSR 2) in 47% patients and in 20.5% patients with chemoresistant disease (CRD). All except one patient were in stage III/IV, extranodal site of disease had 24 patients and bulky disease had l0 patients. All the patients received a uniform preparatory regimen (BEAM). Results. An overall response was achieved in 30 of 32 evaluated patients, with 62.5% in CR and 31.25% in PR. After applying radiotherapy, two patients with PR after ASCT reached CR. Median follow-up was 15.5 months (range 3-133 months). The probability of overall survival (OS) and progression-free survival (PFS) at a 3-year period for all patients was 51.9 % and 48.9%, respectively. For 22 patients in CR after ASCT, a 3-year DFS was 66.5%. Estimates of 2.5-year survival were 14.3%, 61.9% and 100% for CRD, CSR and for patients with CR/PR, respectively (p < 0.01). However, when patients undergoing consolidation were analyzed separately from those in CSR, no significant difference in OS and PFS was observed according to the disease status at ASCT. In univariate analysis for OS, PFS i DFS, extranodal site of disease and disease bulk had no predictive value. Twelve patients died. The main cause of death was Hodgkin's disease. Transplant-related mortality was 3.1%. One patient with CRD developed secondary acute myeloid leukemia and died 28 months after the transplantation. Conclusion. Autologous SCT is efficient as consolidation therapy in high-risk patients and in chemosensitive relapse, but it has no benefit in patients with chemoresistant disease.